Scientific-practical conference with international participation "Revision prosthetics: current state and prospects of solving problems" - Kostrub, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article presents the materials of scientific-practical conference with international participation "Revision hip and knee arthroplasty: current status and prospects of solving the problems", which took place in Ivano-Frankivsk on March 12-13, 2015.